Realization of a 594 Wh kg−1 Lithium‐Metal Battery Using a Lithium‐Free V2O5 Cathode with Enhanced Performances by Nanoarchitecturing (Small 1/2023). Issue 1 (4th January 2023) - Sim, Kiyeon; Kwon, JunHwa; Lee, Seungmin; Song, Hayong; Cho, Ki‐Yeop; Kim, Subin; Eom, KwangSup
Abstract : Lithium Metal Batteries In article number 2205086, KwangSup Eom and co‐workers present the lithium‐free cathode of nanoplate‐stacked V2 O5 (VO) for high‐energy lithium metal batteries (LMBs). The kinetics and capacity of VO are significantly increased by enhancing the Li + diffusion via the engineering of the crystal growth. The LMB employing VO has high specific energy and Coulombic efficiency, simultaneously.